Relatos de adultos mayores sobre el afrontamiento del Abandono Familiar “Fundación Desarrollo y Amparo Social”. San Miguel. 2021. - Velecela Romero, Darwin Patricio (2021)
Introduction: Abandonment is not fulfilling certain duties, not providing the necessary assistance and accompaniment care for the elderly, according to según (Ruiz C & Hernández, 2021) Purpose: To reveal the experiences of the elderly in the face of family abandonment in the gerontological center “Fundación de Desarrollo y Amparo Social” in the city of San Miguel, through an in-depth interview, to learn about their experience. Methodology: The present case study is of a qualitative type with a Phenomenological and Hermeneutical approach, an in-depth interview previously validated by a professional was applied, with the participation of 8 older adults who met the inclusion criteria, after signing the consent informed; The qualitative analysis software ATLAS TI was used, a hermeneutical unit was elaborated which consists of hierarchy of codes, memos, citations and networks, in the analysis it divided 4 core categories, with their respective subcategories. Results: Older adults clearly perceive what family abandonment is and their current situation in the gerontological center when they find themselves helpless and isolated from their loved ones, living with caregivers and other older adults has been a significant support in their coping with the difficult situation, they state that the influencing factors for their family members to abandon them were their advanced age, their sufferings and the lack of time to attend to their needs, the activities arranged by the staff represent a fundamental pillar in the maintenance of their health and good health. mood. Conclusions: Older adults express feeling helpless, isolated, forgotten and rejected from their environment, despite having relatives, they consider the gerontological center as their new home where they can actively cope with their last stage of aging, they say they are resigned to it. fact of having been abandoned by their family. Keywords: Elderly, abandonment, loneliness, care, feelings